Red Cell Distribution Width and Risk of Atrial Fibrillation and Subsequent Thromboembolism: The Tromsø Study - Hald, Erin Mathiesen; Løchen, Maja-Lisa; Lappegård, Jostein; Ellingsen, Trygve; Mathiesen, Ellisiv B.; Wilsgaard, Tom; Njølstad, Inger; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (TH Open, 2020)
Introduction - Red cell distribution width (RDW) is associated with cardiovascular diseases, including atrial fibrillation (AF) and venous thromboembolism (VTE). Whether RDW is a risk marker for thromboembolic events in AF patients is scarcely known. We aimed to assess the association between RDW and the risk of AF, and AF-related VTE and ischemic stroke, in a population-based cohort. Methods - We measured RDW in 26,111 participants from the Tromsø Study (1994–1995), and registered incident AF cases through December 31, 2013. Among participants with AF, first-ever VTEs and ischemic strokes were registered from the date of AF diagnosis through the end of follow-up. We calculated hazard ratios (HRs) with 95% confidence intervals (CIs) for AF by quartiles of RDW. Furthermore, we calculated cause-specific HRs for VTE and ischemic stroke by tertiles of RDW for participants with AF. Results - There were 2,081 incident AF cases during a median of 18.8 years of follow-up. Subjects with RDW in the highest quartile (RDW ≥ 13.3%) had 30% higher risk of AF than those in the lowest quartile (RDW ≤ 12.3%). Among those with AF, subjects with RDW in the upper tertile had a doubled risk of ischemic stroke (HR 2.07, 95% CI 1.20–3.57). In contrast, RDW was not associated with incident VTE in subjects with AF. Conclusion - RDW was significantly associated with incident AF in a general population. Among subjects with AF, high RDW was associated with ischemic stroke, but not VTE.